Un General Data Protection Regulation (GDPR) non molto general - Elena Bougleux (Archivio Antropologico Mediterraneo)
Anthropological research and social research in general are facing the restrictions and the new data management procedures established by the new European regulation, established in 2018. Before analyzing the technical merits of what is still possible to do and how to do it in compliance with current regulations, the essay discusses to what extent the concept of data as understood by the GDPR fits the case of our discipline. The essay analyzes the genesis and specificity of anthropological data, mainly ethnographic data, and raises epistemological and procedural issues related to the different nature of data in anthropology and in other disciplines. Recalling various traditions of studies – in philosophy, history, cultural criticism and linguistic – which have deeply discussed the genesis of knowledge, the essay highlights the limitations and risks of an approach that proposes a single management for a multiplicity of variable and non-reducible research circumstances.